APPLICATION OF NIGHT-TIME LIGHTING IN NON-COMMERCIAL PUBLIC SPACES BASED ON RICHARD KELLY’S THREE PRINCIPLES OF LIGHTING DESIGN Case Study: Siwalankerto Town Road Corridor: PENERAPAN PENCAHAYAAN RUANG PUBLIK NON-KOMERSIAL MALAM HARI BERBASIS TIGA ASAS PERANCANGAN PENCAHAYAAN RICHARD KELLY Studi Kasus : Koridor Jalan Kampung Kota Siwalankerto - Margareth Sunjoto (Ide dan Dialog Desain Indonesia (Idealog), 2025)
Abstract: This paper aims to discuss alternative design concepts for nighttime lighting in non-commercial public spaces using Richard Kelly’s three principles of lighting design. This study uses the village street corridors of Siwalankerto, Surabaya, as a case study. This is based on the issues and phenomena surrounding the implementation of nighttime lighting in urban village street corridors that use the SNI 7391:2008 standard, which emphasizes technical aspects such as illuminance levels. The requirement for specific illuminance levels is then met through the use of public street lighting (LPJU) without considering other supporting aspects that shape the urban village. This study aims to illustrate how urban village street corridors at night can be designed by considering the characteristics and activity needs of the surrounding residents. This research is a qualitative study using a single-case study approach. The case study subject is the Siwalankerto urban village street corridor, which has previously been studied in terms of both compliance with street lighting standards and the lighting preferences of the surrounding community as the primary users. The analysis of the case study is presented through the depiction of three lighting techniques: ambient luminescence, focal glow, and play of brilliant. The results of this study seek to examine the lighting of the urban village street corridor from the perspective and considerations of the human scale as the primary users. It is hoped that this will serve as a basis for reflection on development and new ideas in the lighting design of non-commercial public spaces, such as urban village street corridors. Keywords: urban village street corridors, lighting design, village street lighting, Richard Kelly’s three principles of lighting design